The Effect of Sales Promotion on Purchasing Decisions on Customer Loyalty of Brand Beverages Re.Juve - Agung Febra Pinota (International Journal of Social Service and Research, 2023)
This study aims to determine whether the influence of sales promotion on the purchase decision of the Re-Juve brand, to find out whether the influence of purchasing decisions on customer loyalty of the Re-Juve brand, to find out whether the influence of purchase decisions can mediate the influence between sales promotion and customer loyalty. The data used is primary data, namely from the results of questionnaires conducted by 150 respondents, these respondents are respondents who buy Re-Juve branded drinks from markets and websites in Jakarta. The research model is quantitative with the analysis used starting with the formation of an optimal portfolio and continuing To test each variable, namely promotion and purchase decisions on customer loyalty, a t test is used, while to test the effect together using the f test. The results showed that sales promotion affects purchasing decisions, purchasing decisions affect customer loyalty, and purchasing decisions can mediate the influence between sales promotion and customer loyalty.